Improving Employee Performance Through Financial Motivation, Teamwork, and Leader Supervision at PT. Kusuma Energi Mentari - Saputri, Arum Wulan; Endah Amaliyah, Erlina Dewi (Admisi dan Bisnis, 2024)
PT. Kusuma Energi Mentari providing renewable energy using solar panels. Work targets increasing every year, means that the company is well developed. However, the increase in work targets has not been realized optimally. Therefore, PT. Kusuma Energi Mentari strives to improve their employee performance. This research was conducted to find out what factors can influence employee performance at PT. Kusuma Energi Mentari, especially in term of financial motivation, teamwork, and leader supervision. Those factors needs to be re-examined because there are inconsistent results from previous research. The sample was 32 employees or used saturation sampling technique. Data was obtained using questionnaire and tested using multiplier linier regression analysis in SPSS 23 application. The results show that financial motivation, teamwork, and leader supervision partially and simultaneously have a positive effect on employee performance. It means when the salary, allowances, bonuses, incentives, and protection programs provided by the company   going higher, the quality, quantity of work, sense of resposibility, teamwork, and initiative in the employees will be higher too. If the sense of responsibility in the team, the sense of mutual contribution, maximizing ability, coordination in the process of completing task, and effective communication within the team member increase, it will increse the quality, quantity of work, sense of resposibility, teamwork, and initiative in the employees too. When the setting of work standars, work assessment, work measurement, and analysis of work deviations improve, it will improve the the quality, quantity of work, sense of resposibility, teamwork, and initiative in the employees too